Pengaruh Pemberian Jerami Pada Tanah Untuk Kelembapan Tanah - Lawolo, Todermanto (CV. SINAR HOWUHOWU, 2025)
Soil moisture is a crucial factor influencing plant growth and agricultural land productivity. One effective natural method to maintain soil water content is the utilization of straw as mulch or organic matter. This study was conducted through a literature review by analyzing a number of scientific journals that discussed the effects of straw application on soil physical characteristics, particularly the soil’s ability to retain water. The findings indicate that straw plays a multifunctional role, such as reducing the rate of water evaporation, improving soil structure and aggregation, and increasing organic matter content. In addition, straw supports soil microbial activity and helps stabilize soil temperature. This review recommends the use of straw as part of conservative and environmentally friendly farming practices to support sustainable soil water resilience.